Peripheral Blood DNA Methylation Changes in Response to Centella asiatica Treatment in Aged Mice - Olivia Monestime; Brett A. Davis; Cora Layman; Kandace J. Wheeler; Wyatt Hack; Jonathan A. Zweig; Amala Soumyanath; Lucia Carbone; Nora E. Gray (Biology)
Alterations in epigenetic modifications, like DNA methylation, in peripheral blood could serve as a useful, minimally invasive biomarker of the effects of anti-aging interventions. This study explores this potential with a water extract of the botanical Centella asiatica (CAW). Eighteen-month-old mice were treated with CAW in their drinking water for 5 weeks alongside vehicle-treated eighteen-month-old C57BL6 mice. Reduced representation bisulfite sequencing (RRBS) was used to identify genome-wide differential methylation in the blood of CAW-treated aged mice compared to vehicle-treated aged mice. Our results showed a distinct enrichment of differentially methylated regions (DMRs) nearby genes involved in biological processes relevant to aging (i.e., antioxidant response, metabolic regulation, cellular metabolism). A distinct difference was observed between males and females in both the number of methylation sites and the state of methylation. Moreover, genes nearby or overlapping DMRs were found to be enriched for biological processes related to previously described cellular effects of CAW in the mouse brain (i.e., antioxidant response, metabolic regulation, calcium regulation, and circadian rhythm). Together, our data suggest that the peripheral blood methylation signature of CAW in the blood could be a useful, and readily accessible, biomarker of CAW’s effects in aging.